When corporate social responsibility motivates employee citizenship behavior: The sensitizing role of task significance - Ong, Madeline; Mayer, David M.; Tost, Leigh P.; Wellman, Ned (Organizational behavior and human decision processes, 2018)
•Task significance moderates the relationship between CSR and employee OCB.•When task significance is high, CSR is more positively associated with OCB.•These effects are mediated by prosocial motivation, not alternative mechanisms.•We find support for our moderated-mediation model in 3 field studies. Scholars have proposed that organizations’ corporate social responsibility (CSR) efforts are often positively associated with employees’ organizational citizenship behaviors (OCB) and have invoked identity-based mechanisms to explain this relationship. Complementing these perspectives, we develop a CSR sensitivity framework that explains how task significance, a micro-level job characteristic, can sensitize employees to their organizations’ macro-level CSR efforts, thereby strengthening the association between CSR and OCB. Across three field studies, we find that CSR and task significance interact to predict OCB, such that an organization’s CSR is more positively associated with OCB among employees who report higher task significance than among those who report lower task significance. Furthermore, we find support for prosocial motivation as a mediator of this interactive effect, but we do not find evidence for several alternative mediators. We discuss the implications of our findings for the literatures on CSR, job design, and other-oriented approaches to organizational behavior.